Expression and functional evaluation of ABC and SLC transporters in Human Choroid Plexus Papilloma (HIBCPP) cells: a human blood-cerebrospinal fluid barrier model - Kurosawa, Toshiki; Ohtsuki, Sumio; Ishikawa, Hiroshi; Schroten, Horst; Schwerk, Christian; Kubo, Yoshiyuki; Deguchi, Yoshiharu (Pharmaceutical research, 2025)
Human choroid plexus papilloma (HIBCPP) cells derived from choroid plexus papilloma in the lateral ventricle are considered suitable model cells for the blood-cerebrospinal fluid barrier (BCSFB). Therefore, in this study, the transporters expressed in HIBCPP cells were identified, and the functions of representative transporters were evaluated.
Gesehen am 12.01.2026